Potential nutritive value of some tree leaves commonly used for small ruminant in the Aegean region of Turkey - Ünlü, Hayrullah Bora; Özkan, Çağrı Özgür; Kamalak, Adem (Progress in Nutrition, 2022)
The nutritional potential of the leaves of 10 different maquis tree species were evaluated in terms of chemical composition, in vitro gas and methane production, metabolizable energy (ME) and organic matter digestibility (OMD) in a maquis and mountainous region of western Turkey. Leaves from 10 tree species, Quercus aucheri, Olea europaea, Quercus robur, Morus alba L, Paliurus spina-christi, Pistacia terebinthus, Punica granatum, Pyrus elaeagnifolia, Vitis vinifera, and Tilia cordata, were sampled from maquis areas. Tree species had a significant effect on the chemical composition, in vitro gas, methane production, ME, and OMD (P